The safety and efficacy of carbon nanoparticle suspension injection versus indocyanine green tracer-guided lymph node dissection during radical gastrectomy (FUTURE-01): A single-center randomized controlled trial protocol - Tian, Yuan; Pang, Yue; Yang, Peigang; Guo, Honghai; Liu, Yang; Zhang, Ze; Ding, Pingan; Zheng, Tao; Li, Yong; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; et al. (Frontiers in Oncology, 2023)
Background The use of lymph node (LN) tracers can help obtain a complete dissection of the lymph nodes and increase the detection rate of LNs and metastatic LNs. Carbon nanoparticle suspension injection (CNSI) and indocyanine green (ICG) have been widely used in radical gastrectomy in recent years. Nevertheless, the comparison of their clinical effects has not been studied. Method/design The FUTURE-01 trial will be the first randomized, open-label, single-center trial to compare CNSI and ICG. The study started in 2021 and enrolled 96 patients according to a prior sample size calculation. The primary outcome is the number of LNs retrieved. The secondary outcomes are LN staining rate, LN metastasis rate, stained LN metastasis rate, perioperative recovery and survival. Conclusion By comparing the safety and efficacy of CNSI and ICG tracer-guided LN dissection in patients with gastric cancer, we can determine the most appropriate LN tracer at present. With the help of LN tracers, the operation is simplified, and the prognosis of these patients is improved. Our study is a prospective exploration of the safety, efficacy, and prognosis of CNSI and ICG. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT05229874?cond=NCT05229874&draw=2&rank=1, identifier NCT05229874.